To multiply the mixed number \(-1 \frac{1}{6}\) by \(7\), first convert the mixed number into an improper fraction.
-
Convert \(-1 \frac{1}{6}\) to an improper fraction: \[ -1 \frac{1}{6} = -\left(1 \times 6 + 1\right)/6 = -\frac{7}{6} \]
-
Next, multiply \(-\frac{7}{6}\) by \(7\): \[ -\frac{7}{6} \times 7 = -\frac{7 \times 7}{6} = -\frac{49}{6} \]
-
Now, convert \(-\frac{49}{6}\) back to a mixed number: \[ -\frac{49}{6} = -8 \frac{1}{6} \] (since \(49 \div 6 = 8\) with a remainder of \(1\))
Thus, the answer is: \[ \boxed{-8 \frac{1}{6}} \]